Revolution! the explosion of world cinema in the 60s - Cowie, Peter (Faber and Faber Limited, 2006)
From across the world young film-makers emerged from nowhere to challenge the dreary conformity of the 50s and flout the taboos (both sexual and political) of their age. The foot-soldiers in this revolution included Godard, Truffaut, Pasolini and Bertolucci, Oshima and Forman and Polanski and Cassavetes. Peter Cowie was in the thick of this cultural foment, not least when some of these firebrands shut down the Cannes film festival in the heady May of 1969. This title recaptures the cultural mood of the 60s through numerous interviews with key film-making talents of the time. (source: Nielsen Book Data)